2014
DOI: 10.1021/ma502180c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Interactions Mediate Hierarchical Self-Assembly of POSS-Containing Block Copolymers Blended with Phenolic Resin

Abstract: P o l y( me t h y l m et h a c r y l a t e ) -b -poly-(methacryloyl polyhedral oligomeric silsesquioxane) (PMMA-b-PMAPOSS) block copolymers of various compositions were prepared through anionic living polymerization. We employed differential scanning calorimetry, Fourier transform infrared spectroscopy, small-angle X-ray scattering, transmission electron microscopy, and wide-angle X-ray diffraction to investigate the miscibility, specific interactions, and hierarchical self-assembly of PMMA-b-PMAPOSS block cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 70 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…[41][42][43] Onion-like microspheres have received much attention due to their potential application as carriers for controlled-release systems; 44 onion-like morphologies have been reported widely in the bulk state, formed from triblock copolymers, copolymer/homopolymer blends, and copolymer/copolymer blends, where thermodynamic equilibrium plays an important role. 45,46 In this study, we observed onion structures of various sizes and with different numbers of ring patterns [ Fig. 9(a)].…”
Section: Self-assembly Of Ps-b-pvbt/a-peo Supramolecular Complexes Inmentioning
confidence: 81%
“…[41][42][43] Onion-like microspheres have received much attention due to their potential application as carriers for controlled-release systems; 44 onion-like morphologies have been reported widely in the bulk state, formed from triblock copolymers, copolymer/homopolymer blends, and copolymer/copolymer blends, where thermodynamic equilibrium plays an important role. 45,46 In this study, we observed onion structures of various sizes and with different numbers of ring patterns [ Fig. 9(a)].…”
Section: Self-assembly Of Ps-b-pvbt/a-peo Supramolecular Complexes Inmentioning
confidence: 81%
“…PMMA-b-PMAEtPOSS and PMMA-b-PMAIBPOSS were synthesized by living anionic polymerization. 17,18 The domain sizes of microphase separation listed in Table 1 were obtained by bulk small angle x-ray scattering measurements. As the NL material, polymethylmethacrylate-r-polymethacryli-buty lPOSS-r-polyglycidylmethacrylate (PMMA-r-PMAIBPOSSr-PGMA) was utilized.…”
Section: Methodsmentioning
confidence: 99%
“…They have unique star-shaped nanostructures and chemical properties, such as facile chemical modification, 55 good pH tolerance, high temperature and oxidation resistance properties [21][22][23] . So far, micro/mesoporous materials based on POSS precursors have been prepared by various chemical routes including hydrosilation methods, thermolysis, and coppermediated coupling [24][25][26][27] . However, there are little reports on the 60 preparation of POSS-derived micro/mesoporous poly(ionic liquid) materials for catalysis.…”
Section: Introductionmentioning
confidence: 99%